Rapid synthesis of tin oxide nanostructures by microwave-assisted thermal oxidation for sensor applications - S. Phadungdhitidhada (2018)
© 2017 Vietnam Academy of Science & Technology . In the present work nanostructures of tin oxides were synthesized by a microwave-assisted thermal oxidation. Tin precursor powder was loaded into a cylindrical quartz tube and further radiated in a microwave oven. The as-synthesized products were characterized by scanning electron microscope, transmission electron microscope, and x-ray diffractometer. The results showed that two different morphologies of SnO 2 microwires (MWs) and nanoparticles (NPs) were obtained in one minute of microwave radiation under atmospheric ambient. A few tens of the SnO 2 MWs with the length of 10-50 μm were found. Some parts of the MWs were decorated with the SnO 2 NPs. However, most of the products were SnO 2 NPs with the diameter ranging from 30-200 nm. Preparation under loosely closed system lead to mixed phase SnO-SnO 2 NPs with diameter of 30-200 nm. The single-phase of SnO 2 could be obtained by mixing the Sn precursor powders with CuO 2 . The products were mostly found to be SnO 2 nanowires (NWs) and MWs. The diameter of SnO 2 NWs was less than 50 nm. The SnO 2 NPs, MWs, and NWs were in the cassiterite rutile structure phase. The SnO NPs was in the tetragonal structure phase. The growth direction of the SnO 2 NWs was observed in (1 1 0) and (2 2 1) direction. The ethanol sensor performance of these tin oxide nanostructures showed that the SnO-SnO 2 NPs exhibited extremely high sensitivity.